Variação de preços, bens, insumos e serviços para a piscicultura no Oeste do Paraná - Esteves, Yago Alves (2021)
The state of Paraná is the largest national producer of fish, producing 120 thousand tons in 2019, highlighting the western region, which has one of the main production centers in Brazil. The construction of a price index for a given region is of fundamental importance for analyzing the behavior of local economic agents, so this work aimed to analyze the temporal behavior of the price of fish farming inputs, developing monthly variation indices, based on in the theory of relative price index number. The research was carried out in the different links of the fish farming production chain in the western region of Paraná, through telephone calls to 13 suppliers of goods, inputs and services. The automation values for fish farming do not vary greatly over the months, the price of a thousand fry varies according to the beginning of the productive harvest, keeping its price stable until the beginning of the next harvest, the feed price is influenced by the variation of its ingredients, production phase and amount of crude protein. In August 2020 it was responsible for the biggest increase in the price of the tilapia kg (38.46%), and in December of the same year the filet kg increased by 11.54% This study concludes that it is important to analyze the variations so that, in the future, variation indices can be created that can support investment projects and activity costs.